2020
DOI: 10.33506/sl.v9i2.970
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Consumer Satisfaction in Mediating Service Quality and Brand Image on Consumer Loyalty

Abstract: Tujuan dari penelitian ini adalah untuk menganalisis peran kepuasan kerja dalam memediasi pengaruh kualitas layanan dan citra merek terhadap loyalitas konsumen di Toko Sepatu Padang Holic. Populasi dan sampel penelitian adalah 80 konsumen Holic Shoes Shop Padang. Teknik pengumpulan sampel menggunakan metode sensus dengan model penelitian Structural Equation Modeling (SEM) dengan alat uji analisis menggunakan perangkat lunak SmartPLS 3. Hasil penelitian menyimpulkan bahwa kualitas layanan dan kepuasan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
1
1
1
Order By: Relevance
“…The level of contentment among SSS members is not significantly influenced by gender in this study. In the study by Maryanti, Sukmana, and Faezal, there is no differentiation observed in the levels of satisfaction and loyalty among male and female consumers (Maryanti et al, 2022). This finding further substantiates the data result.…”
Section: Level Of Satisfaction Of Sss Memberssupporting
confidence: 78%
See 2 more Smart Citations
“…The level of contentment among SSS members is not significantly influenced by gender in this study. In the study by Maryanti, Sukmana, and Faezal, there is no differentiation observed in the levels of satisfaction and loyalty among male and female consumers (Maryanti et al, 2022). This finding further substantiates the data result.…”
Section: Level Of Satisfaction Of Sss Memberssupporting
confidence: 78%
“…In the same way that sex can result in disparities in customer contentment, female customers are more content than their male counterparts (Aljasser and Sasidhar, 2016). However, these results are in contrast with the research conducted by Maryanti, Sukmana, and Faezal, which does not discover any differentiation in the levels of satisfaction and loyalty among male and female consumers (Maryanti et al, 2022). According to the research of Pereira, Salgueiro, and Rita, gender moderates the relationship between knowledge and satisfaction (Pereira et al, 2016).…”
Section: Literature Reviewcontrasting
confidence: 76%
See 1 more Smart Citation
“…Penelitian menunjukkan bahwa kepuasan pelanggan berpengaruh terhadap pembelian ulang (Saintz, 2018). Penelitian lain menunjukkan bahwa kepuasan pelanggan mempengaruhi loyalitas pelanggan (Bayu Putra et al, 2020). Kepuasan pelanggan juga mampu sebagai mediator antara beberapa variabel bebas terhadap variabel loyalitas pelanggan.…”
Section: Pengaruh Kepuasan Konsumen Terhadap Keputusan Pembelian Kembaliunclassified